Economics of Social Issues - W. Grimes Paul (Mc Graw Hill, 2008)
Sharp/Register/Grimes’ Economics of Social Issues originated the Social Issues approach to teaching basic economic principles. Designed as an introduction to general economics for non-majors, it presents economic concepts as useful tools to analyze contemporary social issues. Each chapter presents economic concepts then places them within the context of very current issues facing society. The book may also be used to supplement principles courses with lively social issues to add relevance to the economic principles being taught.